Nickel-based tri-reforming catalyst for the production of synthesis gas - Kang, Jung Shik; Kim, Dae Hyun; Lee, Sang Deuk; Hong, Suk In; Moon, Dong Ju (ELSEVIER, 2007)
The tri-reforming reaction was carried out over NiO-YSZ-CeO2 catalyst to produce a synthesis gas from greenhouse gases like CH4 and CO2 contributing to the greenhouse effect. The NiO-YSZ-CeO2 catalysts were characterized by N-2 physisorption, X-ray diffraction (XRD), transmission electron microscope (TEM) and scanning electron microscope (SEM) techniques. It was found that the tri-reforming reaction was more favorable than the dry reforming reaction for the production of synthesis gas. It was also observed that NiO-YSZ-CeO2 catalyst showed higher catalytic activity and stability than commercial Holder Topsoe (HT) and Imperial Chemical Industries (ICI) catalysts in the tri-reforming of CH4. The results suggest that the tri-reforming process can be applied to the production of high-valued chemicals and the fuel processor of solid oxide fuel cell (SOFC) and molten carbonate fuel cell (MCFC) systems. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: CARBON-DIOXIDE; SUPPORTED RH; METHANE; CO2; CH4; SYNGAS; STEAM